Recirculating structures and combustion characteristics in a reverse-jet swirl pulverized coal burner. (15th June 2020) - Song, Minhang; Huang, Qian; Niu, Fang; Li, Shuiqing
Graphical abstract: Highlights: Characterization of a novel reverse-jet swirl pulverized coal burner was conducted. Effects of the bluff body and secondary air flowrate were examined. Mechanisms of the recirculating, combustion and NO x formation were revealed. Improvements to combustion stability, burnout and NO x reduction have been done. Abstract: Industrial pulverized coal boilers play an important role in the use of distributed energy, but still suffer from severe pollutant emissions, combustion instabilities and poor fuel adaptabilities. In this paper, numerical simulation and full-scale experiments were carried out to study the recirculating and combustion characteristics of a novel reverse-jet swirl pulverized coal burner with an adding bluff body and flexibly adjusted secondary air. The axial velocity stagnation contour and the out-of-plane vorticity contour were used to characterize the recirculation structure of reverse swirl flows. The original design achieves a moderate char burnout with the carbon content in fly ash to be 18.63% under a residence time of 0.158 s, which demands for the further improvements. However, if only the injection velocity of the secondary air is increased by halving the axial range of the swirl vane, the recirculating flow is strengthened to such an undesired degree that coal ignition appears in the primary air pipe, the burner-wall overheating and near-wall particle enrichment can occur. To overcome it, a bluff body was incorporated with the enhanced secondary air flow. The recirculation zone was restricted downstream the bluff body, thus eliminating possible early coal ignition. Besides, the width of the recirculating flow is broadened, resulting in a more stable combustion with a less fluctuated pressure signal at the furnace exit. The near-wall coal particle concentration is reduced by approximately 90%. As a result, the use of bluff body decreased the carbon content in fly ash to 8.55% by increasing the coal particle residence time to 0.171 s. In addition, the NO concentration at the burner outlet is decreased by 8% owing to a longer coal particle residence time in the reducing environment.